School corporal punishment : Public perceptions on using the methods to discipline the students / Hirmayani Tahir ... [et al.] - Tahir, Hirmayani; Maimin, Siti Suharah (2015)
Most of the people had experienced situations of corporal punishment, especially during their school sessions either in secondary or high school and some of them have suffered from the incidences do not have any courage to tell their parents because they might think that it is allowed to be done by the teachers. Corporal punishment is the practice of physical force with the purpose of causing the children pain but it is for the means of correction and controlling the child's behavior (Gershoff E. T., 2002). It is a common situation where punishment uses to modify a person's behavior or to discipline as what happen in school till today. However, to the extent to which it gives an impact towards the student's growth in school either can help to prevent unethical behavior or put them in a bad environment in which school as a place they supposed to learn and gain knowledge. Furthermore, corporal punishment, including spanking or slapping on the head, which not being classified as abuse which as long as no marks are left over a relatively short period of time. So, to distinguish physical abuse and corporal punishment, two factors need to be consider which is the force and the intention.